PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MATERI PELAJARAN MENGGAMBAR FLORA DAN FAUNA DI SMP - Sasmita Miradj; I Wayan Sudana; Isnawati Mohamad (Widyadari, 2025)
Learning media is an important instrument that needs to be developed to improve students' understanding of the subject matter, but not all teachers are able to develop learning media according to the subject matter. This study aims to develop audio-visual learning media to improve students' understanding of the material on drawing flora and fauna. The study used the Research and Development (R&D) method with the 4D model: define, design, development, and dissemination. Data were collected through interviews, observations, documentation, and assessment sheets for material validation, media feasibility, and media effectiveness. Data analysis was carried out qualitatively and quantitatively. The results show that the development of audio-visual learning media for drawing flora and fauna material can be done through four stages: 1) definition, namely conducting historical analysis, facilities and infrastructure, resources and curriculum; 2) design, namely compiling learning materials, editing process for learning media and dubbing; 3) development, namely realizing videos into audio-visual learning media, with a material validation score of 98.07% (very valid), a feasibility score of 90.63% (very feasible), and an effectiveness score of 89.19% (very effective); 4) distribution by providing the media to schools for learning to draw flora and fauna. It is concluded that the developed audio-visual learning media can be used effectively in learning to draw flora and fauna in Junior High Schools.